Experimental demonstration of harmonic mode-locking in Sb2Se3-based thulium-doped fiber laser. (November 2021) - Ma, Xiaohui; Chen, Wu; Tong, Liang; Liu, Shaoqing; Dai, Wenwen; Ye, Shanshan; Zheng, Ziqi; Wang, Yangyang; Zhou, Yong; Zhang, Wei; Fang, Wentan; Chen, Xiaolin; et al.
Highlights: Experimental demonstration of mode-locked fiber laser based on Sb2 Se3 saturable absorber for the first time. Harmonic mode-locking from the 2nd to the 31st order in 2 μm waveband. The highest operating frequency of 693 MHz that has ever been demonstrated in a Sb2 Se3 -based fiber laser. Abstract: Studies have shown that Sb2 Se3 had the potential to be used as an optical switch or a mode-locker. However, the actual performance of its optical switch capability in fiber lasers has not been proved yet. In this paper, we experimentally demonstrate the nonlinear optical modulation characteristics and optical switch capabilities of Sb2 Se3 with a harmonic mode-locked thulium-doped fiber laser (TDFL). The nonlinear modulation depth and saturation power of Sb2 Se3 -based SA at 1930 nm are 9.3% and 4.08 kW, respectively. The fundamentally mode-locked pulses operate at the central wavelength of 1961.35 nm have the 3-dB bandwidth of 4.57 nm, repetition rate of 22.36 MHz and pulse width of 890 fs. The 2th to 31th harmonic mode locking (HML) are observed, corresponding to the pulse repetition rates ranging from 44.7 to 693 MHz. To the best of our knowledge, this is the highest operating frequency that has ever been demonstrated in a Sb2Se3-based fiber laser. The experimental results indicate that Sb2 Se3 could be a promising candidate for generating ultrashort pulses with high repetition rates.